Solving Fuzzy Volterra Integrodifferential Equations of Fractional Order by Bernoulli Wavelet Method - R. Mastani Shabestari; R. Ezzati; T. Allahviranloo (Advances in Fuzzy Systems)
A matrix method called the Bernoulli wavelet method is presented for numerically solving the fuzzy fractional integrodifferential equations. Using the collocation points, this method transforms the fuzzy fractional integrodifferential equation to a matrix equation which corresponds to a system of nonlinear algebraic equations with unknown coefficients. To illustrate the method, it is applied to certain fuzzy fractional integrodifferential equations, and the results are compared.